P63 Fifteen year trends in HIV diagnoses among men who have sex with men in the united kingdom: 1999–2013. (18th May 2015) - Desai, Sarika; Croxford, Sara; Brown, Alison; Mitchell, Holly; Hughes, Gwenda; Delpech, Valerie
Abstract : Background/introduction: As in many other western countries, men who have sex with men (MSM) are most affected by HIV in the UK. Aim(s)/objectives: To describe 15-year trends in HIV among MSM to inform prevention strategies. Methods: National HIV surveillance data were linked to national register deaths and HIV testing data from sexually transmitted infection (STI) clinics. Multivariable analyses revealed predictors of late diagnosis (<350 copies/mL) and mortality. Results: Between 1999–2013, 37, 560 MSM (aged ≥15) were diagnosed with HIV; diagnoses increased from 1, 440 (1999) to 3, 250 (2013). The majority of men were white (85%) and UK-born (68%). Probable UK-acquisition was high (81%) including among those born abroad (66%). Median CD4 count rose, 350 cells/mm 3 to 463 cells/mm 3 . Despite a decline in late diagnosis (50% to 31%), >800 men have been diagnosed late annually since 2004. HIV testing in STI clinics in England increased, 10, 900 to 102, 600. One-year death rates among new diagnoses declined (4.6% to 0.9%) due to fewer deaths among late presenters (4.4% to 1.8%). Older age (>50) and living outside London were predictors of late presentation, while older age and late presentation were predictors of one-year mortality. Discussion/conclusion: In its third decade, the HIV epidemic among UK MSM has continued to diversify. Increases in new diagnoses reflect both increased testing and ongoing transmission. Despite improvements in patient outcomes, >800 men present late each year; death rates remain high and preventable. Culturally appropriate prevention and testing strategies require strengthening to reduce HIV transmission and late diagnosis.